2019
DOI: 10.1111/pace.13626
|View full text |Cite
|
Sign up to set email alerts
|

Shorter cryoballoon applications times do effect efficacy but result in less phrenic nerve injury: Results of the randomized 123 study

Abstract: BackgroundThe second‐generation cryoballoon significantly improves outcome of pulmonary vein isolation (PVI) but may cause more complications than the first generation. Currently, no consensus regarding optimal cryoballoon application time exists. The 123‐study aimed to assess the minimal cryoballoon application duration necessary to achieve PVI (primary endpoint) and the effect of application duration on prevention of phrenic nerve injury (PNI).MethodsPatients <75 years of age with paroxysmal atrial fibrillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 30 publications
0
28
1
Order By: Relevance
“…Although cryoablation is effective and safe in patients with paroxysmal AF undergoing ablation, 2 the optimal freezing strategy to induce durable lesions while minimizing complications is still under discussion. In previous studies, shorter applications decreased success in achieving PVI 9 . On the other hand, some studies have shown that prolonging freezing time does not improve outcomes.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Although cryoablation is effective and safe in patients with paroxysmal AF undergoing ablation, 2 the optimal freezing strategy to induce durable lesions while minimizing complications is still under discussion. In previous studies, shorter applications decreased success in achieving PVI 9 . On the other hand, some studies have shown that prolonging freezing time does not improve outcomes.…”
Section: Discussionmentioning
confidence: 89%
“…However, the optimal freezing strategy is still under debate 3–7 . Prolonged freezing cycles may achieve more durable PVI at the cost of longer procedures and an increased risk of injury to extracardiac structures (eg, phrenic nerve, esophagus, bronchial tree) 8–10 . Conversely, insufficient times may be associated with greater recurrence 9 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As an example, it would be expected that TTI ED is extended when the cryoballoon is ablating along a thickened cardiac anatomy such as the ridge between PV and left atrial appendage. Ultimately, our computational model data might further progress dosing strategies and algorithms that continue to attempt to shorten the cryoablation freeze duration …”
Section: Discussionmentioning
confidence: 99%